2020
DOI: 10.1136/bmjopen-2020-038416
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality in patient education and health literacy: a scoping review protocol

Abstract: BackgroundHealth literacy enables the patients in understanding the basic healthcare information and taking informed health decisions; thus, it is a desirable goal of any healthcare system. It increases patients’ adherence to treatment, improves the quality of care and eases the overall burden on the healthcare system. In recent years, technological solutions are being increasingly used in educating patients and achieving better health literacy. Augmented reality (AR) provides powerful, contextual and situated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 46 publications
0
20
0
2
Order By: Relevance
“…Lynch and Urakov emphasized that although AR is promising in the OR, it need not only apply to the spine surgeon with instrumentation. There has been a growing push in health literacy to use tools such as AR to help a patient fully understand the details of their care [ 29 ]. Already in the fields of Nephrology and Urology, 3D visualization using AR has shown a higher level of understanding of location, size and surgical options for tumor management [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lynch and Urakov emphasized that although AR is promising in the OR, it need not only apply to the spine surgeon with instrumentation. There has been a growing push in health literacy to use tools such as AR to help a patient fully understand the details of their care [ 29 ]. Already in the fields of Nephrology and Urology, 3D visualization using AR has shown a higher level of understanding of location, size and surgical options for tumor management [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each mode offers a different focus and a different aspect of meaning and, therefore, differently influences human cognition [20]. The computer, tablet, or smartphone is a tool for construction and dissemination of communication; therefore, digital technology opens up the possibility of using many different modes, and no specialized knowledge is required to activate additional modes [7] [8] [26]. It is also observed that modalities are co-constructed between patients and the clinic since patients use online resources to co-construct their own patchwork of communication bundles; however, this implies that the hospital, to improve communication and counteract potential inequalities between various groups of patients resulting from these wider semiotic practices, needs to know much more about how patients, in their social context, create value from various modes of communication.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), patients with limited health literacy skills risk having a poorer health outcome and higher treatment costs. Improving health literacy skills can therefore have a positive effect on patient health outcomes, address health inequities, and reduce economic burden [4] [5] [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence proves that MR learning fosters long-term retention of learning content, increases motivation, and encourages teamwork [23]. Thus far, however, the vast majority of studies on MR learning focus on the education and training of healthcare professionals (i.e., physicians and nurses), while only a narrow set of studies shed light on the patient aspect of this [13]. Thus, Jakl et al [23] developed and tested a mobile-based augmented reality prototype to educate strabismus patients about eye surgeries based on interactive 3D storytelling.…”
Section: Figure 1 Ppe Using Vsi Pe [7]mentioning
confidence: 99%
“…To date, however, little is known regarding patients' perception of MR glasses in healthcare [13]. Klinker et al [14], who examined whether patients would accept healthcare services involving smart glasses, found that they reduce patients' willingness to consent to medical procedures, as the devices increase risk perceptions and decrease patients' assessment of healthcare professionals' skills.…”
Section: Introductionmentioning
confidence: 99%